S-parameter characterization and lumped-element modelling of millimeter-wave single-drift impact-ionization avalanche transit-time diode - Zhang, Wogong; Yamamoto, Yuji; Oehme, Michael; Matthies, Klaus; Raju, Ashraful I.; Srinivasan, V. S. Senthil; Koerner, Roman; Gollhofer, Martin; Bechler, Stefan; Funk, Hannes; Tillack, Bernd; Kasper, Erich; et al. (Japanese Journal of Applied Physics, 2016)
Five silicon (Si) p++-n%-n++ samples were grown at various doping concentrations (1.0 × 1017-2.2 × 1017cm-3) in an n- layer by using the reduced-pressure CVD technique. By using these samples, 30 × 2μm2 single-drift (SD) impact-ionization avalanche transit-time (IMPATT) diodes were processed with Si-based monolithic millimeter-wave integrated circuit (SIMMWIC) technology.1,2) The samples within a small process window exhibited a large negative differential resistance at approximately the avalanche frequency, as confirmed by small-signal S-parameter characterization. A model based on depletion width was given to explain the conditions for the appearance of the negative differential IMPATT resistance, which is the basis of millimeter-wave amplifier and oscillator applications. Furthermore, a measurement-based small-signal lumpedelement model was established to describe the IMPATT functionality from the circuit component aspect. This lumped-element model shows a negative differential resistance within a well-defined range in the given element parameters, which can explain the experimental observations.
CRIS-Team Scopus Importer:2021-06-29